CritCom: assessment of quality of interdisciplinary communication around deterioration in pediatric oncologic patients - Rivera, Jocelyn; Malone, Sara; Puerto-Torres, Maria; Prewitt, Kim; Counts, Lara; Wiphatphumiprates, Parima; Sakaan, Firas; Al Zebin, Zebin; Arias, Anita V.; Bhattacharyya, Parthasarathi; Gunasekera, Sanjeeva; Johnson, Sherry; et al. (Frontiers in Oncology, 2023)
Background: High-quality clinical care requires excellent interdisciplinary communication, especially during emergencies, and no tools exist to evaluate communication in critical care. We describe the development of a pragmatic tool focusing on interdisciplinary communication during patient deterioration (CritCom).The preliminary CritCom tool was developed after a literature review and consultation with a multidisciplinary panel of global experts in communication, pediatric oncology, and critical care to review the domains and establish content validity iteratively. Face and linguistic validity were established through cognitive interviews, translation, and linguistic synthesis. We conducted a pilot study among an international group of clinicians to establish reliability and usability.Results: After reviewing 105 potential survey items, we identified 52 items across seven domains. These were refined through cognitive interviews with 36 clinicians from 15 countries. CritCom was piloted with 433 clinicians (58% nurses, 36% physicians, and 6% other) from 42 hospitals in 22 countries. Psychometric testing guided the refinement of the items for the final tool. CritCom comprised six domains with five items each (30 total). The final tool has excellent reliability (Cronbach's alpha 0.81-0.86), usability (93% agree or strongly agree that the tool is easy to use), and similar performance between English and Spanish tools. Confirmatory factor analysis was used to establish the final 6-domain structure.Conclusions: CritCom is a reliable and pragmatic bilingual tool to assess the quality of interdisciplinary communication around patient deterioration for children in diverse resource levels globally. Critcom results can be used to design and evaluate interventions to improve team communication.